Optimization of post-combustion CO2 process using DEA-MDEA mixtures - Rodriguez, Néstor (2011)
This paper presents optimal operating conditions for the post-combustion CO2 capture process utilizing aqueous amine solutions obtained using a process simulator (HYSYS). Three alkanolamine solutions (Methyldiethanolamine MDEA, DiEthanolAmine DEA and MDEA-DEA mixture) are considered to study the performance of the capture process.The design problem addressed in this paper requires specifying the optimal operating conditions (inlet and outlet temperature of the lean solution stream on the absorber, CO2 loading, amine composition and flow rates, among others) to achieve the given CO2 emission targets at a minimum total annual cost. A detailed objective function including total operating costs and investment is considered.The influence of the variation of CO2 reduction targets and the mixing proportion of amines on the total annual cost is analyzed in detail. Numerical results are presented and discussed using different case studies.The results demonstrate that process simulators can be used as a powerful tool not only to simulate but also to optimize the most important design parameters of the post-combustion CO2 capture process.